The impact of sport-related concussion history on neck strength in elite Australian rules football and rugby league athletes - Kavyani, A.; Bourne, M.; Williams, M.; Timmins, R.; Peek, K.; Bennett, H.; Mastrorocco, M.; Garrett, J. M. (Physical Therapy in Sport, 2025)
Objectives To investigate whether sport-related concussion (SRC) history (including recency and total numbers) is associated with maximal isometric neck strength in elite Australian rules football (ARF) and rugby league (ARL) athletes.